OP29 ST2+/IL-33 responsive cells promote tumorigenesis in colitis-associated colorectal cancer. (25th January 2019) - Lopetuso, L R; De Salvo, C; Di Martino, L; Goodman, W; Scaldaferri, F; Armuzzi, A; Gasbarrini, A; Pizarro, T T
Abstract: Background: IL-33 and its receptor, ST2, are important factors in the pathogenesis of IBD. Emerging evidence suggests its critical role the potential contribution to inflammation-driven tumorigenesis that can lead to colorectal cancer (CRC). The aim of our study was to characterise the precise contribution of IL-33/ST2 axis in the azoxymethane (AOM)/dextran sodium sulphate (DSS) model of colitis-associated CRC. Methods: C57/BL6 wild-type (WT), IL-33 KO, ST2 KO, and CD73 KO mice were given a single dose of AOM (7.4 mg/kg) followed by two cycles of 3% DSS for 7 days in drinking water. Disease activity index (DAI), as well as endoscopic and histological evaluation of colons, were performed. IHC, immunofluorescence (IF), and qPCR were done on full-thickness colons for IL-33 and ST2 localisation and identification, as well as mRNA expression, respectively. FACS analysis was performed on cell suspensions from resected, isolated polyps and qPCR for Vimentin, Desmin, αSMA, CD34, CD31, CD73 was completed on sorted cells in order to functionally characterise ST2+/IL-33 responsive cells. Results: IL-33, ST2L, and sST2 mRNA transcripts were dramatically elevated in AOM/DSS-treated WT mice vs. controls. IHC of treated WT mice revealed localisation of IL-33 to the colonic epithelium and to cells within the LP morphologically consistent with tissue macrophages. ST2 staining was localised to the intestinal epithelium in tissues immediately adjacent to tumours, while within the tumours themselves, ST2+ cells displayed a spindle/fibroblast-like morphology with a unique distribution throughout the polyps. Little to no staining for both IL-33 and ST2 was present in controls. Using IF, ST2 co-localised with αSMA in polyps; however, ST2 staining was not exclusive for αSMA+ cells. FACS analysis showed a distinct population of CD45+ haematopoietic cells consisting of CD3/CD8+ cytotoxic T cells (CTLs), CD19+ B-lymphocytes, CD11b+CD11c- and CD11b+CD11c+ myeloid cells. ST2 was mainly expressed by CTLs, and CD11b+CD11c- and CD11b+CD11c+ myeloid cells. Non-haematopoietic cells (CD45-) also expressed ST2. At qPCR, CD45-ST2+ and CD45+ST2+ expressed significantly elevated levels of CD73 vs. ST2- cells. AOM/DSS treatment in IL-33, ST2 KO, and CD73KO mice resulted in a significant decreased polyp number and size vs. WT, with colonoscopy revealing the development of protruding lesions with abnormal vascular patterns, suggesting pre-tumorous lesions in WT mice, while all KO mice showed their absence with a more impressive mucosal inflammation, likely due to reduced epithelial proliferation and repair caused by the deficiency of IL-33 signalling. Conclusions: Our results suggest that the IL-33/ST2 axis promotes tumorigenesis in colitis-associated CRC through the activation of CD73.